Quality Blood Sampling Techniques and Influence of Socio-cultural Factors among ARVs Forces Community in Seeking Healthcare - Silali, Maurice B.; Wanzala, Maximila; Owino, Denis O.; Muhonja, Faith (SMU Medical Journal, Volume – 3, No. – 1, January, 2016, 2016)
Project monitoring and evaluation (M/E) determines resource accountability and its impact to various stakeholders. Plenary project success requires holistic community participation and empowerment. However, this approach remains unexplained in developing countries to ascertain the relevance, effectiveness, efficiency, outcome and sustainability of Donor initiated projects. It was these reasons that M/E study was carried out in Forces ARVs clinic, to evaluate the trend uptake of quality blood sampling techniques, and influence of socio-cultural factors in seeking healthcare. Globally over 44 million projects initiated by developing partners are not evaluated to determine their future sustainability. In Kenya few private sectors do evaluation to measure project achievements. Furthermore 80% of projects initiated by Donors at community in our society, underscore in profits due to low uptake of community participation and appropriate technology utilization. By formal survey and rapid appraisal methods, data was collected based on problem based learning and community based education feedbacks on importance of quality blood sampling technique, Patient initiated counseling, testing approach and positive social change, determined by qualitative and quantitative sampling tools . Over 80%, positive impacts on project was noted with greater social change formulation concepts towards health seeking behaviors among ARVs households, due to consistence improved quality blood sampling techniques and overall healthcare that decreased the ill health and poverty in vicious cycle.
Keywords: Appropriate technology; Monitoring & evaluation; Community participation; Sampling technique; Social change; Socio cultural